Implementasi Konseling Terhadap Pecandu Napza Di Yayasan Rehabilitasi Natura Addiction Center Jambi - Muhammad Yamin (Jurnal Pendidikan Indonesia (JOUPI), 2023)
This research was conducted at the Jambi Natura Addiction Center Rehabilitation Foundation. This research is motivated by the problem of narcotics abuse at the Natura Addiction Center Rehabilitation Foundation. This prompted the writer to research. This research aims to add to the body of knowledge in the field of rehabilitation counseling for narcotics abusers. To increase the knowledge of the writer both theoretically and practically in field research. can be useful for other researchers who are interested in conducting the same research but taking from different aspects. The research approach that the authors use is descriptive qualitative. Data collection was carried out by observation, interview and documentation techniques. Determination of research subjects using purposive sampling technique. Data analysis techniques were carried out by data reduction, data presentation and drawing conclusions as well as verification of the reliability of research results obtained by triangulation techniques to meet the criteria of credibility, transferability, dependability and objectivity.The results of this study indicate the implementation of the counseling guidance program at the Natura Addiction Center Jambi Rehabilitation Foundation. Drug victims include learning ethics and manners, communication and relationships, group dynamics, motivational guidance and entrepreneurship guidance. The techniques are Integrated Counseling (KT), Individual Counseling (KI), Group Guidance (BKL), Family Counseling (KK). Enthusiastic in participating in guidance counseling, counselors who are experienced and master material for adequate facilities and infrastructure and have been equipped with experienced nurses and counselors. Inhibiting Factors: Human Resources are still lacking, there are clients who still feel inferior to themselves, Lack of available personnel who are capable of lobbying and making approaches to drug addicts or abusers or their families.